STADE‐HF (sST2 As a help for management of HF): a pilot study. (13th March 2020) - Huet, Fabien; Nicoleau, Jean; Dupuy, Anne‐Marie; Curinier, Corentin; Breuker, Cyril; Castet‐Nicolas, Audrey; Lotierzo, Manuela; Kalmanovich, Eran; Zerkowski, Laetitia; Akodad, Mariama; Adda, Jérôme; Agullo, Audrey; et al.
Abstract: Aims: Biomarkers are not recommended until now to guide the management of patients with heart failure (HF). Soluble suppression of tumorigenicity 2 (sST2) appears as a promising biomarker. The current study considered pre‐discharged sST2 values as a guide for medical management in patients admitted for acute HF decompensation, in an attempt to reduce hospital readmission. Methods and results: STADE‐HF was a blinded prospective randomized controlled trial and included 123 patients admitted for acute HF. They were randomized into the usual treatment group (unknown sST2 level) or the interventional treatment group, for whom sST2 level was known and used on Day 4 of hospitalization to guide the treatment. The primary endpoint was the readmission rate for any cause at 1 month. It occurred in 10 patients (19%) in the usual group and 18 (32%) in the sST2 group without statistical difference ( P = 0.11). Post hoc analysis in the whole group shows that the mean duration of hospitalization was lower in patients with low sST2 (<37 ng/mL) at admission vs. high sST2 (8.5 ± 9.5 vs. 14.8 ± 14.9 days, respectively, P = 0.003). In addition, a decrease in sST2 greater than 18% is significantly associated with a lower readmission rate. Conclusions: Soluble suppression of tumorigenicity 2‐guided therapy over a short period of time does not reduce readmissions. However, sST2 was clearly associated with duration of hospitalization, and the decrease in sST2 was associated with decreased rehospitalizations. Long‐term outcome using sST2‐guided therapy deserves further investigations.